Bracero-Priests: The Vatican's Response to Mexican Migration, 1942-1964. - OLSON, MADELEINE CLAIRE (Catholic Historical Review)
This article examines Operation Migratory Labor (O.M.L.), a crossborder collaboration between the Mexican and United States Catholic hierarchies, guided by Vatican authorities, from 1953-1964, which brought Mexican priests into the United States to tend to Bracero migrants and to protect them from Protestant missionization. Employing Vatican sources in tandem with Mexican documentation, this article demonstrates the geopolitical ramifications of this surge of migration in distinctively religious terms. O.M.L. heralded a new era of transnational migratory pastoral care and revealed how intertwined the institutional and pastoral concerns of the Mexican Catholic Hierarchy were during the 1940s and 1950s.